Pilaster: From a small detail to great mysteries - Kapustin, Petr (project baikal, 2021)
Within the last century, a lot has been said pejoratively about the pilaster, when accusing it of imitativeness, figurativeness and all other manner of offenses concerning architectural forms. “Pilaster!” almost became a specific architectural curse in those years. It seemed that the pilaster itself simply wished it looked like a modest shadow of a column. Whenever it appears, however, it signifies restoration of the right of the wall. But the phenomenon of the wall is too ancient to be treated carelessly or disrespectfully. The pilaster seems to contain a lot of mystery, including the very mystery of the origin of architecture.
Keywords: pilaster; order; “truthfulness”; lie in architecture; authenticity in architecture; succession and eternity in architecture